Magnitude Assessment of Adult Neurogenesis in the Octopus vulgaris Brain Using a Flow Cytometry-Based Technique - Di Cosmo, Anna; Bertapelle, Carla; Porcellini, Antonio; Polese, Gianluca (Frontiers in Physiology, 2018)
Abstract Adult neurogenesis is widespread among metazoans, it occurs in animals with a network nervous system, as cnidarians, and in animals with a complex and centralized brain, such as mammals, non-mammalian vertebrates, ecdysozoans and a lophotrochozoan, Octopus vulgaris. Nevertheless, there are important differences among taxa, especially in the number of the regions involved and in cell proliferation rate during the life-cycle. The comparative evaluation of adult neurogenesis among different brain regions is an arduous task to achieve with only stereological techniques. However, in Octopus vulgaris we recently confirmed the presence of active proliferation in the learning-memory centres, multisensory integration centres, and the motor centres of the adult brain. Here, using a flow cytometry technique, we provide a method to quantify the active proliferation in Octopus nervous system using a BrdU in vitro administration without exposing the animals to stress or painful injections usually used. This method is in line with the current animal welfare regulations regarding cephalopods, and the flow cytometry-based technique enabled us to measure adult neurogenesis more quickly and reliably than histological techniques, with the additional advantage of processing multiple samples in parallel. Flow cytometry is thus an appropriate technique for measuring and comparing adult neurogenesis in animals that are in a different physiological and/or environmental contexts. A BrdU immunoreactivity distribution, to define the neurogenic areas, and the effective penetration in vitro of the BrdU is also provided.